Pengaruh Kredibilitas Pegawai dalam Komunikasi Interpersonal Terhadap Sikap Nasabah Pada Perusahaan - Surbakti, Nurhayati; Silalahi, Siska Maria Eviline (Business Administration Study Program - Universitas Katolik Parahyangan, 2008)
To communicate and create good relationship with its customers, a companyâs employeesmust always make an effort to understand and serve the customers so they aresatisfy and loyal. In order to get effective interpersonal communication adequate withits customers, the employees must focus on confidence, immediacy, interaction management,expressiveness, and other orientation. The main purpose of the research,using association method, is to show the employees role as the communicator sothe customers can trust them. The result shows that the employeesâ credibility oninterpersonal communication and customersâ attitude are quite good and there issignificant correlation between them.Keywords: Employee Credibility, Interpersonal Communication, Customer Attitude